Una Posible Villa Romana en Villafáfila (Zamora) - Rodríguez Hernández, José (Zephyrvs, 2009)
RESUMEN: A 3 km. al NE. de Villafáfila (Zamora) y dentro de una zona arqueológica abundante en restos romanos, se halla emplazada la posible villa romana. Realizada una prospección en el lugar, dio pobres resultados pero a juzgar por los elementos materiales encontrados (especialmente cerámicos) es dable suponer que la probable villa existía ya en el siglo II p. C. ABSTRACT: The possibly Roman villa is to be found at about three kilometers and at the North-Eeast of Villafáfila (Zamora), within an archeological area rich in roman remnants. A visit and prospection of the site itself gave poor results, but, judging from material elements found there (especially ceramics) we assume that this villa was already in existence in the second century p. C.